Gross Revenue for VAT Tax: Evidence of Differentiation at the Portuguese Littoral Municipalities - Correia, Pedro Miguel Alves Ribeiro; Catarino, João Ricardo (Revista del CLAD Reforma y Democracia, 2016)
This article presents the current VAT system in Portugal as a particular case of the wider reality of the member States of the European Union. The document exposes, as its main objective, the statistical testing of the existence of differences in the taxable gross revenue for VAT purposes at the end of the first decade of the XXI century, among the Portuguese municipalities at the Interior, Coast and Islands. The data used corresponds to the taxable gross revenue for VAT purposes in the 308 municipalities of Portugal. The detected differences in taxable gross revenue levels for VAT purposes between the three geographical areas analyzed are significant, reinforcing the results obtained in other studies. The research and detection of similar results in South American nations is proposed.
Keywords: Tax; Taxation; Value Added Tax; Regions; Regional Disparity; Portugal